Measurement of the distribution of ^207Bi depositions on calibration sources for SuperNEMO. (23rd July 2021) - Arnold, R.; Augier, C.; Barabash, A.S.; Basharina-Freshville, A.; Birdsall, E.; Blondel, S.; Bongrand, M.; Boursette, D.; Breier, R.; Brudanin, V.; Busto, J.; Calvez, S.; et al.
Abstract: The SuperNEMO experiment will search for neutrinoless double-beta decay (0νββ), and study the Standard-Model double-beta decay process (2νββ). The SuperNEMO technology can measure the energy of each of the electrons produced in a double-beta (ββ) decay, and can reconstruct the topology of their individual tracks. The study of the double-beta decay spectrum requires very accurate energy calibration to be carried out periodically. The SuperNEMO Demonstrator Module will be calibrated using 42 calibration sources, each consisting of a droplet of 207 Bi within a frame assembly. The quality of these sources, which depends upon the entire ^207Bi droplet being contained within the frame, is key for correctly calibrating SuperNEMO's energy response. In this paper, we present a novel method for precisely measuring the exact geometry of the deposition of 207 Bi droplets within the frames, using Timepix pixel detectors. We studied 49 different sources and selected 42 high-quality sources with the most central source positioning.